1992
DOI: 10.1007/bf01623838
|View full text |Cite
|
Sign up to set email alerts
|

Can vigorous exercise play a role in osteoporosis prevention? A review

Abstract: Part of the reduction in bone density observed in older people is due to disuse rather than the aging process itself. While some mechanical stress is needed to maintain optimal bone density, it is not clear just which types of exercise are most valuable or whether appropriate exercise might reduce the need for estrogen therapy in postmenopausal women. Cross-sectional studies. Physical activity, aerobic fitness, and strength have all been correlated with bone density. Young people who use a specific part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
3
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(102 citation statements)
references
References 103 publications
3
88
3
6
Order By: Relevance
“…Immobilization by SCI causes general bone loss, which ranges from 30 to 50%. 2,[8][9][10][11] The results of our study confirm that there is a significant decrease of bone mass in patients after SCI, especially rapid in lower extremities. BieringFSorensen et al reported 50% BMD decrease in paralyzed extremities during 3 years longitudinal study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Immobilization by SCI causes general bone loss, which ranges from 30 to 50%. 2,[8][9][10][11] The results of our study confirm that there is a significant decrease of bone mass in patients after SCI, especially rapid in lower extremities. BieringFSorensen et al reported 50% BMD decrease in paralyzed extremities during 3 years longitudinal study.…”
Section: Discussionsupporting
confidence: 80%
“…8 A number of studies have been conducted on weightbearing effects on bone mass at different skeletal sites. [9][10][11][12][13][14] Some studies 15,16 have shown the influence of passive weight-bearing on BMD, but these findings were not confirmed by other researchers. [17][18][19][20] The aim of the study was to assess bone loss in persons with SCI and its dependence on weight-bearing activity (passive standing) during the first 2 years post injury.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that physical activity may explain some observations on BMD and bone structure, particularly in males (Agarwal, 2001). Numerous studies have reported the association between physical activity and bone gain (Gutin & Kasper, 1992;Recker et al, 1992;Turner et al, 1992). Greater bone density in weightlifters, compared with control subjects, has been shown by Davee et al (1990).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and vitamin D supplements appear to be effective in preventing bone loss in women, particularly in postmenopausal and with low habitual Ca intake (<400mg/day). [5][6][7] Despite being a common problem, majority of the women are unaware of it. Awareness varies widely according to the level of education.…”
Section: Introductionmentioning
confidence: 99%